Complex crop rotations improve organic nitrogen cycling. (February 2023) - Breza, Lauren C.; Mooshammer, Maria; Bowles, Timothy M.; Jin, Virginia L.; Schmer, Marty R.; Thompson, Bennett; Grandy, A. Stuart
Abstract: Nitrogen (N) availability in agroecosystems is often poorly coupled to plant N uptake, leading to inefficient fertilizer use and environmental losses. Building soil organic N pools and enhancing internal recycling of N with crop rotations while reducing synthetic inputs may help improve N use efficiency. The organic N pool could be a valuable source of N that could help farmers reduce reliance on large inorganic N inputs if controls on its availability were better understood. While we know that the breakdown of high-molecular weight organic N compounds is the rate-limiting step to accessing bioavailable N from organic sources in natural ecosystems, there has been little work in agroecosystems to identify how management influences this inflection point in the N cycle. To provide insight into how growers can manage the organic N pool to reduce fertilizer input, we examined gross protein depolymerization rates within an agricultural context. Specifically, we investigated 1) how crop rotations affect organic N pools and alter the rate of organic N cycling, and 2) whether inorganic N fertilization enhances, has no effect, or suppresses soil N cycling responses to crop rotation. To test this, we measured gross rates of protein depolymerization, amino acid consumption, mineralization, and ammonium consumption using 15 N isotope pool dilution assays on soils collected from a long-term crop complexity experiment near Mead, NE, USA. Treatments sampled included both 0 kg and 180 kg N ha −1 fertilization levels in continuous corn, corn-soybean, and corn-soybean-sorghum-oat/clover rotations. We found that higher cropping complexity coupled with zero fertilization increased gross depolymerization and amino acid consumption rates by 193% and 93%, respectively, relative to fertilized, monocrop plots. Gross mineralization was 2.7 and 3.9x higher in complex rotations than corn-soybean and continuous corn rotations, respectively, while ammonium consumption was 4x higher in fertilized plots than unfertilized plots across all cropping regimes. We show that within our study system internal N cycling is stimulated by cropping system complexity; however, N fertilization suppresses some of the benefits of temporal crop diversification. Balancing reduced mineral fertilizer application rates with increased cropping complexity has the potential to promote internal N cycling while minimizing N losses in agroecosystems. Highlights: Quantified gross amino acid production and consumption in agricultural soils with a 15 N amino acid pool dilution method. Complex cropping systems increased rates of amino acid cycling. High nitrogen fertilization suppressed amino acid cycling in complex cropping systems. A combination of increased rotational complexity and minimized fertilization may optimize internal nitrogen cycling.